2014
DOI: 10.1017/s107407080002914x
|View full text |Cite
|
Sign up to set email alerts
|

Apple Export Competition between the United States and China in the Association of Southeast Asian Nations

Abstract: We developed a trade model under imperfect competition to analyze the market power of U.S. and Chinese apple producers in the Association of Southeast Asian Nations (ASEAN) market and their domestic markets and the elimination of ASEAN tariffs on U.S. and Chinese apples. We also formulated welfare functions for the United States, China, and ASEAN. Comparative static results are derived to analyze the effect of tariff changes on exports, domestic sales, and welfare. Based on the theoretical model, we derived an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
(10 reference statements)
2
6
0
Order By: Relevance
“…The reason could be those two countries export fresh apples through the entire year, focusing on the first two quarters, whereas Chile exports only in the second and third quarters (Giacinti, 2016). This finding concurs with Luckstead, Devadoss, and Mittelhammer (2014) who found that the United States and China are competitors in ASEAN countries. Conditional cross-price elasticities between China and South Africa in the fresh pear market are statistically significant and positive, which means that the two countries compete in this market.…”
Section: India Fresh Apple Conditional Demand Elasticitiessupporting
confidence: 91%
See 2 more Smart Citations
“…The reason could be those two countries export fresh apples through the entire year, focusing on the first two quarters, whereas Chile exports only in the second and third quarters (Giacinti, 2016). This finding concurs with Luckstead, Devadoss, and Mittelhammer (2014) who found that the United States and China are competitors in ASEAN countries. Conditional cross-price elasticities between China and South Africa in the fresh pear market are statistically significant and positive, which means that the two countries compete in this market.…”
Section: India Fresh Apple Conditional Demand Elasticitiessupporting
confidence: 91%
“…Overall, demand for imported fresh apples would increase by 24%. This coincides with findings by Luckstead, Devadoss, and Mittelhammer (2014) in that tariff elimination would favor U.S. apple producers, and U.S. apple exports would displace Chinese apple exports to India.…”
Section: India Fresh Apple Welfare and Demand Change Estimationsupporting
confidence: 89%
See 1 more Smart Citation
“…The Asian market, including countries such as China, Taiwan, Vietnam, Thailand and India, is becoming a promising apple export destination for European, American and Australasian apple producers. However, these markets set high quality standards and require constant product innovation [18,[20][21][22][23][24].…”
Section: Trends In the Apple Industrymentioning
confidence: 99%
“…Few studies have examined imperfect competition under trade protection and expansionary policies in agricultural commodity markets. Luckstead, Devadoss, and Mittelhammer (2014a) analyzed imperfect competition between U.S. and Chinese apple exports to ASEAN using homogenous products and strategic trade theory. Luckstead, Devadoss, and Mittelhammer (2015) have also applied strategic trade theory to study the U.S. and Brazil orange juice markets.…”
Section: Theoretical Model and Analysismentioning
confidence: 99%